Immunohistochemical expression of p53, ki-67, tenascin, and fibronectin in giant cell fibroma and traumatic fibroma of the oral mucosa - Gomes de Oliveira, Ingrid; Aparecida Silva da Costa, Adriana; Pereira Meirelles, Daniela; Soares Tavares, Thalita; de Jesus Viana Pinheiro, João; Alves de Mesquita, Ricardo; Campolina Rebello Horta, Martinho; Carlos Caldeira, Patrícia (Journal of Oral Diagnosis, 2024)
Objective: This study aimed to compare the immunoexpression of p53, ki-67, tenascin, and fibronectin between giant cell fibroma (GCF) and traumatic fibroma (TF), in order to explore a benign neoplastic or a reactive nature of GCF. Methods: A cross-sectional study was conducted. Samples of GCF and TF were retrieved from the files of Oral Pathology Service, matched by site and size. Immunohistochemistry for p53, ki-67, tenascin, and fibronectin was evaluated in the superficial and deep regions of the lesions using the Image J Software. The number of positive cells was determined for p53 and ki-67, and the positive area was established for tenascin and fibronectin. Statistical analysis was performed with Mann-Whitney and independent t-tests (p≤0.05). Results: Comparing to TF, GCF showed higher expression of p53 protein in superficial (p=0.009) and deep regions (p=0.027), as well as higher tenascin expression in deep regions (p=0.000). Ki-67 and fibronectin immunoexpression did not differ between GCF and TF (p>0.05). Conclusions: The results of the present study seem supportive of a benign neoplastic nature of GCF, rather than a reactive one, especially considering the p53 and tenascin expression. Further studies with larger samples and broader markers should confirm this hypothesis.